Hypoxia inhibits semicarbazide-sensitive amine oxidase activity in adipocytes. (15th August 2015) - Repessé, Xavier; Moldes, Marthe; Muscat, Adeline; Vatier, Camille; Chetrite, Gérard; Gille, Thomas; Planes, Carole; Filip, Anna; Mercier, Nathalie; Duranteau, Jacques; Fève, Bruno
Highlights: Semicarbazide-sensitive amine oxidase (SSAO) is likely involved in endothelial damage during the course of diabetes and obesity. Hypoxia inhibits SSAO activity in adipocytes, in vitro, in a model of murine adipocytes, and in vivo, in a rat model of hypoxia. This effect is time- and concentration- dependent and seems to be mediated by the variations of the acid-base equilibrium. Hypoxia-induced down-regulation of SSAO activity could represent an adaptive mechanism to lower toxic molecules production. Abstract: Semicarbazide-sensitive amine oxidase (SSAO), an enzyme highly expressed on adipocyte plasma membranes, converts primary amines into aldehydes, ammonium and hydrogen peroxide, and is likely involved in endothelial damage during the course of diabetes and obesity. We investigated whether in vitro, adipocyte SSAO was modulated under hypoxic conditions that is present in adipose tissue from obese or intensive care unit. Physical or pharmacological hypoxia decreased SSAO activity in murine adipocytes and human adipose tissue explants, while enzyme expression was preserved. This effect was time-, dose-dependent and reversible. This down-regulation was confirmed in vivo in subcutaneous adipose tissue from a rat model of hypoxia. Hypoxia-induced suppression in SSAO activity was independent of the HIF-1-α pathway or of oxidative stress, but was partially antagonized by medium acidification. Hypoxia-induced down-regulation of SSAO activity could represent an adaptive mechanism to lower toxic molecules production, and may thus protect from tissue injury during these harmful conditions.